1977
DOI: 10.1042/bj1670557
|View full text |Cite
|
Sign up to set email alerts
|

The separation and characterization of bronchial glycoproteins by density-gradient methods

Abstract: 1. Sputum samples from a total of 18 asthmatic and chronic bronchitic patients were examined by analytical density-gradient ultracentrifugation. CsBr was used as the dispersal agent and dense electrolyte. 2. The patterns show two main groups of components, banding at about 1.3g/ml and 1.5g/ml; in addition, a few samples showed a further zone at approx. 1.65g/ml. These components were identified as protein, secretory glycoprotein and DNA respectively. The glycoprotein zone was frequently hypersharp, and usually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(46 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…For electrophoretic and immunoblot analysis, DU-PAN-2 antigen was also purified by cesium bromide density gradient centrifugation (6) V, overnight in the cold. The sheet was then incubated with 5% bovine serum albumin at 40°C followed by DU-PAN-2 antibody or a control antibody at room temperature for 1 hr with continuous rocking.…”
Section: Methodsmentioning
confidence: 99%
“…For electrophoretic and immunoblot analysis, DU-PAN-2 antigen was also purified by cesium bromide density gradient centrifugation (6) V, overnight in the cold. The sheet was then incubated with 5% bovine serum albumin at 40°C followed by DU-PAN-2 antibody or a control antibody at room temperature for 1 hr with continuous rocking.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason they can be almost completely separated from non-cova]ently bound protein by equflibrium centrifugation in density gradients of highly concentrated cesium salt solutions. This method was used successfully to isolate mucous glycoproteins from pig gastric mucosa [1], from human ovarian cyst fluids [7], from sputum [8] and from cervical mucus [9]. In the experiments described in this paper gastric mucous glycoproteins from rat were isolated on cesium chloride gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Since proteinases in the C F LM-gel samples fragmented radiolabeled tracheobronchial mucin In vitro (Fig. 4), proteinases in LM-gel samples from pathological airways may account for the variations in molecular weight, solubility, and chromatographic behavior reported for tracheobronchial mucins (6,(37)(38)(39)(40)(41)(42)(43)46). This study has also demonstrated that TBM from healthy individuals exhibited physical and chemical properties similar to those of TBM from a patient with bronchial asthma (5).…”
Section: Discussionmentioning
confidence: 59%
“…4) The cysteine contents of the CF lung mucins analyzed were considerably lower than those of normal and asthmatic mucins, and similar to values obtained on analysis of the proteolytically-digested glycopeptide fragments of asthmatic mucin (39,40). However, considerable variability in the cysteine concentrations of tracheobronchial mucins has been reported (5,6,33,(38)(39)(40)(41)(42)(43) and cysteine is often not measured quantitively as it requires almost a mg of purified mucin for accurate measurements in duplicate.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation